Pixantrone induces cell death through mitotic perturbations and subsequent aberrant cell divisions - Beeharry, Neil (Cancer Biol Ther, 2015)
Pixantrone is a novel aza-anthracenedione active against aggressive lymphoma and is being evaluated for use against various hematologic and solid tumors. The drug is an analog of mitoxantrone, but displays less cardiotoxicity than mitoxantrone or the more commonly used doxorubicin. Although pixantrone is purported to inhibit topoisomerase II activity and intercalate with DNA, exact mechanisms of how it induces cell death remain obscure. Here we evaluated the effect of pixantrone on a panel of solid tumor cell lines to understand its mechanism of cell killing. Initial experiments with pixantrone showed an apparent discrepancy between its anti-proliferative effects in MTS assays (short-term) compared with clonogenic assays (long-term). Using live cell videomicroscopy to track the fates of cells, we found that cells treated with pixantrone underwent multiple rounds of aberrant cell division before eventually dying after approximately 5 d post-treatment. Cells underwent abnormal mitosis in which chromosome segregation was impaired, generating chromatin bridges between cells or within cells containing micronuclei. While pixantrone-treated cells did not display γH2AX foci, a marker of DNA damage, in the main nuclei, such foci were often detected in the micronuclei. Using DNA content analysis, we found that pixantrone concentrations that induced cell death in a clonogenic assay did not impede cell cycle progression, further supporting the lack of canonical DNA damage signaling. These findings suggest pixantrone induces a latent type of DNA damage that impairs the fidelity of mitosis, without triggering DNA damage response or mitotic checkpoint activation, but is lethal after successive rounds of aberrant division.